Timing of paediatric orchidopexy in universal healthcare systems: international administrative data cohort study. Issue 6 (24th July 2020) - Jay, M. A.; Arat, A.; Wijlaars, L.; Ajetunmobi, O.; Fitzpatrick, T.; Lu, H.; Lei, S.; Skerritt, C.; Goldfeld, S.; Gissler, M.; Gunnlaugsson, G.; Hrafn Jónsson, S.; et al.
Abstract : Background: International guidelines in 2008 recommended orchidopexy for undescended testis at 6–12 months of age to reduce the risk of testicular cancer and infertility. Using administrative data from England, Finland, Ontario (Canada), Scotland and Sweden (with data from Victoria (Australia) and Iceland in supplementary analyses), the aim of this study was to investigate compliance with these guidelines and identify potential socioeconomic inequities in the timing of surgery before 1 and 3 years. Methods: All boys born in 2003–2011 with a diagnosis code of undescended testis and procedure codes indicating orchidopexy before their fifth birthday were identified from administrative health records. Trends in the proportion of orchidopexies performed before 1 and 3 years of age were investigated, as were socioeconomic inequities in adherence to the guidelines. Results: Across all jurisdictions, the proportion of orchidopexies occurring before the first birthday increased over the study period. By 2011, from 7·6 per cent (Sweden) to 27·9 per cent (Scotland) of boys had undergone orchidopexy by their first birthday and 71·5 per cent (Sweden) to 90·4 per cent (Scotland) by 3 years of age. There was limited evidence of socioeconomic inequities for orchidopexy before the introduction of guidelines (2008). Across all jurisdictions for boys born after 2008, there was consistent evidence of inequities in orchidopexy by the first birthday, favouring higher socioeconomic position. Absolute differences in these proportions between the highest and lowest socioeconomic groups ranged from 2·5 to 5·9 per cent across jurisdictions. Conclusion: Consistent lack of adherence to the guidelines across jurisdictions questions whether the guidelines are appropriate. Abstract : International guidelines recommend orchidopexy before 12 months of age. This study, using international administrative health data, found that this was achieved in only a minority of cases and that there were socioeconomic inequities in this outcome. Guidelines not widely applied Abstract : Antecedentes: En el 2008, las guías internacionales recomendaban efectuar una orquidopexia para los testículos no descendidos entre los seis y los 12 meses de edad para reducir los riesgos de cáncer testicular e infertilidad. Utilizando datos administrativos de Inglaterra, Finlandia, Ontario (Canadá), Escocia y Suecia (con datos de Victoria, Australia e Islandia para análisis complementarios), el objetivo de este estudio fue investigar el cumplimiento de estas guías y la identificación de posibles desigualdades socioeconómicas con relación al momento de la cirugía antes de 1 y 3 años de edad. Métodos: A partir de los registros administrativos de salud, se identificaron todos los niños nacidos entre 2003 y 2011 con código diagnóstico de testículos no descendidos y con código de procedimiento correspondiente a orquidopexia antes de cumplir 5 años. Se investigaron las tendencias en la proporción de orquidopexias realizadas antes de 1 y 3 años de edad, respectivamente, al igual que las desigualdades socioeconómicas en el cumplimiento de las directrices de las guías. Resultados: En todas las jurisdicciones, la proporción de orquidopexias realizadas antes del primer año de vida aumentó durante el periodo de estudio. En 2011, del 7, 6% (Suecia) al 27, 9% (Escocia) de los niños habían sido sometidos a orquidopexia en su primer año de vida y del 71, 5% (Suecia) al 90, 4% (Escocia) a los 3 años de edad. Hubo evidencia limitada de las inequidades socioeconómicas para la orquidopexia antes de la introducción de las guías (2008). En todas las jurisdicciones para los niños nacidos después de 2008, hubo evidencia consistente de inequidades para la práctica de una orquidopexia en el primer año de vida en favor de una posición socioeconómica más alta ( socioeconomic position, SEP). Las diferencias absolutas en estas proporciones entre los grupos SEP más altos y más bajos oscilaron entre el 2, 5% y el 5, 9% en todas las jurisdicciones. Conclusión: La falta de adherencia a las guías observada consistentemente en todas las jurisdicciones cuestiona si las guías son apropiadas.